Shishupriya being netramrita - Shobha C. M; Hamsaveni (International Journal of Pharmacy and Analytical Research, 2022)
Milk has an essential micronutrient whose role in visual function has been known for thousands of years. The balance between free radical production and antioxidant defenses in the body helps in controling diseases. Here the study is all about knowing different Ksheera mentioned in the classics for the management of netra rogas as well as swasthya. Stanya is said to be Shishupriya (liked by kids) and surprisingly it also Netramrita (Nector to eyes). Stanya is referred as chakshu shulagna and is used in many preparations mentioned for the treatment of eye disorders. The present study is based on the literary research done on classics to evaluate the importance of stanya, Go Ksheera and Aja Ksheera in Netra Rogas. The study also focused on finding a logical reasoning for the action of stanya in various ocular disorders.